Modo de olhar : metodologia para o estudo de moradias rurais - Pinheiro, Ana Paula Sales Camurça (2011)
Way of approaching: methodology for studying rural residences which relate to the theme of Brazilian rural housing, considering that the previous studies have focused on the urban context. It aims on the problem of the present way of understanding the object of study, which is currently split into specific aspects and spread along different areas of knowledge. It consists on a theme yet not much developed in the scientific fi eld. Consequently, the main goal of this research is to develop a method for studying rural residences with the purpose of contributing either for a better understanding of the object as for the progress of science itself. In order to reach the results, a methodological arrangement was structured considering the previous understanding of rural housing, including the identification of the type as design according to the studies of characterizing and diagnosis and those of proposing character, as well as the particular aspects concerning this object, taking as reference the systematization carried out by Mallard (2005) and the characteristics of self construction by Pina (2004). The arrangement consists of different research techniques that come from several s cience fields and are investigated into the scientific literature and chosen according to specific criteria. Afterwards, the arrangement was imposed on a particular case from which was possible to study the rural residences and it provided the basis for th e analyses of the arrangement itself. The research generated many products along its development, specially the method ology itself and systematization of housing aspects, which can be used in future studies.